2017
DOI: 10.1186/s13104-017-2859-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional control of enterohepatic lipid regulatory targets in response to early cholesterol and phytosterol exposure in apoE−/− mice

Abstract: ObjectiveAn excessive rise in blood lipids during pregnancy may promote metabolic dysfunction in adult progeny. We characterized how maternal phytosterol (PS) supplementation affected serum lipids and the expression of lipid-regulatory genes in the intestine and liver of newly-weaned apo-E deficient offspring from dams fed a chow diet supplemented with cholesterol (0.15%, CH) or cholesterol and PS (2%) (CH/PS) throughout pregnancy and lactation.ResultsSerum lipid concentrations and lipoprotein particle numbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
1
3
1
2
Order By: Relevance
“…In support of these findings, we have recently shown that MHC during the gestation period is associated with hepatic TG accumulation in fetal apoE −/− mice 80 which is similarly linked to a reduction in hepatic lipogenic mRNA expression. This response was similar to what we observed in newly weaned and adult males exposed to MHC throughout gestation and lactation described earlier 74,76 ( Table 2), suggesting that the programming of hepatic dysfunction in adulthood may originate in utero.…”
Section: Excessive Cholesterol Exposure In Gestation Onlysupporting
confidence: 88%
See 2 more Smart Citations
“…In support of these findings, we have recently shown that MHC during the gestation period is associated with hepatic TG accumulation in fetal apoE −/− mice 80 which is similarly linked to a reduction in hepatic lipogenic mRNA expression. This response was similar to what we observed in newly weaned and adult males exposed to MHC throughout gestation and lactation described earlier 74,76 ( Table 2), suggesting that the programming of hepatic dysfunction in adulthood may originate in utero.…”
Section: Excessive Cholesterol Exposure In Gestation Onlysupporting
confidence: 88%
“…In addition to increased hepatic lipid content, 72 newly weaned offspring from hypercholesterolemic apoE −/− mice showed a reduction in hepatic de novo lipogenic gene expression. 74 Similarly, newly weaned pups from hypercholesterolemic hamsters demonstrated increased hepatic cholesterol accompanied with elevated LDLr and HMGCoAr protein content despite no change in SREBP2 protein levels. 73 The adaptations in newly weaned offspring described above can be linked to direct exposure to excessive cholesterol, whether in utero or through the suckling of maternal milk with modified nutrient (e.g., cholesterol, TG) or hormonal composition.…”
Section: Excessive Cholesterol Exposure Throughout Both Gestation Andmentioning
confidence: 96%
See 1 more Smart Citation
“…Gene expression was analyzed using the 2(-delta delta C t) method. Sequences of sense and antisense primers for target and housekeeping genes were based on previously published reports for β-actin, fatty acid synthase (FAS), acetyl-CoA carboxylase (ACC), carnitine palmitoyltransferase 1a (CPT1a), 3-hydroxy-3-methylglutaryl-CoA reductase (HMG-CoAr), sterol regulatory element-binding protein (SREBP) 1c, SREBP2, microsomal triglyceride transfer protein (MTP), diglyceride acyltransferase (DGAT), and apolipoprotein B (apoB) [44].…”
Section: Methodsmentioning
confidence: 99%
“…33 Son çalışmalardan elde edilen bulgular; bitkisel sterollerin bağırsak kolesterolü emilimini (azalmış kolesterol emilimi, artmış fekal kolesterol kaybı) azaltarak ve hepatik kolesterol sentezinde görevli genlerin ifadesini (artan HMG-CoA redüktaz mRNA) değiştirerek kolesterol seviyelerini düşürdüğünü vurgulamaktadır. 14,[34][35][36] Ayrıca, bitkisel sterollerin, 27-hidroksikolesterol üretimi, karaciğer X reseptörü alfa aktivasyonunun inhibisyonu ve insan kolon adenokarsinoma hücre dizisi (Caco-2) enterositlerinde bazolateral sterol taşıyıcısı olan ATP bağlayıcı kaset A1 (ABCA1) ifadesi ile kolesterol emilimini azaltabileceği görüşü de mevcuttur. 37 Randomize kontrollü çalışmaların yer aldığı bir meta analiz çalışmasında, bitkisel sterollerin/stanollerin TK, LDL-K ve trigliserit (TG) konsantrasyonları üzerinde benzer düşürücü etkileri olduğu bildirilmiştir.…”
Section: Bitkisel Sterollerin/stanollerin Aterosklerotik Süreç Ve Kardiyovasküler Hastalıklar üZerine Etkisiunclassified